Faktor–Faktor Yang Berhubungan Dengan Kejadian Pneumonia Pada Balita Di Wilayah Kerja Puskesmas Hanura Kabupaten Pesawaran Tahun 2015 - Cucuk kunang sari; Bambang Setiaji; Agus Widodo (Jurnal Kesehatan, 2022)
Pneumonia is a respiratory infectious disease and is a global health issue in all countries. Based on data from SP2TP Hanura in 2013 the incidence of pneumonia in toddlers was 58 people. The purpose of the study was to determine the factors associated with the incidence of pneumonia in children under five in the working area of ​​the Hanura Health Center, Pesawaran Regency.Type of analytic research with a cross sectional approach, the population is all mothers who have toddlers in the working area of ​​the Hanura Health Center of 639 people. The sample size was 77 people and the sampling technique was simple random sampling. Data analysis using univariate test, bivariate chi square, multivariate using multiple logistic regression. The results of the Chi square test showed that there was no relationship between education (p value = 0.219) and the administration of Vitamin A (p value = 0.330), there was a relationship between nutritional status (p value = 0.219), completeness of immunization (p value = 0.045), age (p value 0.010), the presence of family members who smoke (p value = 0.032) with the incidence of pneumonia in children under five. Age variable is the most dominant variable associated with the incidence of pneumonia in children under five (p value = 0.020). It is hoped that the Hanura Health Center Health Officers can socialize the importance of preventing pneumonia, especially to mothers who have toddlers <2 through counseling using language that is easy to understand, using attractive promotional media such as brochures and leaflets.